Medication Discrepancies in Community Pharmacies in Switzerland: Identification, Classification, and Their Potential Clinical and Economic Impact - Tamara L Imfeld-Isenegger (Pharmacy, 2020)
Background: Transitions of care are high-risk situations for the manifestation of medication discrepancies and, therefore, present threats for potential patient harm. Medication discrepancies can occur at any transition within the healthcare system. Methods: Fifth-year pharmacy students assessed a best possible medication list (BPML) during a medication review (based on medication history and patient interview) in community pharmacies. They documented all discrepancies between the BPML and the latest medication prescription. Discrepancies were classified using the medication discrepancy taxonomy (MedTax) classification system and were assessed for their potential clinical and economic impact. Results: Overall, 116 patients with a mean age and medication prescription of 74 (± 10.3) years and 10.2 (± 4.2), respectively, were analyzed. Of the 317 discrepancies identified, the most frequent type was related to strength and/or frequency and/or number of units of dosage form and/or the total daily dose. Although, the majority of discrepancies were rated as inconsequential (55.2%) on health conditions, the remainder posed a potential moderate (43.2%) or severe impact (1.6%). In 49.5% of the discrepancies, the current patients’ medication cost less than the prescribed. Conclusion: Community pharmacies are at a favorable place to identify discrepancies and to counsel patients. To improve patient care, they should systematically perform medication reconciliation whenever prescriptions are renewed or added.